New Zealand's Oceans Policy - Foster, Angela (Victoria University of Wellington Law Review, 2003)
In light of recent Oceans Policy developments this paper proposes a legal and institutional framework for the management of New Zealand's oceans. It focuses on one key existing problem: the lack of a comprehensive, coherent framework for the sustainable management of the marine environment. The proposed framework addresses this issue by suggesting an overarching statute, based on the approach taken by the Resource Management Act, under which several layers of policy refinement and implementation create national consistency coexisting with localised solutions based on the purpose of sustainability and broad guiding principles. The proposal is consistent with New Zealand's international obligations, other domestic legislation and existing institutional structures. The paper concludes with a statement on the importance to our future well-being of developing a comprehensive and enduring Oceans Policy.